2012
DOI: 10.4161/cc.11.6.19670
|View full text |Cite
|
Sign up to set email alerts
|

Phospho-ΔNp63α-dependent regulation of autophagic signaling through transcription and micro-RNA modulation

Abstract: Cisplatin was shown to induce the ataxia telangiectasia mutated (ATM)-dependent phosphorylation of tumor protein p63 isoform, (ΔNp63α), leading to a transcriptional regulation of specific genes implicated in the control of cell death of squamous cell carcinoma (SCC) cells. We previously observed that the cisplatin-induced phosphorylated (p)-ΔNp63α transcriptionally regulates the expression of specific microRNAs (miRNAs) in SCC cells. We found here that cisplatin exposure of SCC cells led to modulation of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
146
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(149 citation statements)
references
References 89 publications
3
146
0
Order By: Relevance
“…34 By global analysis of microRNA expression, we previously showed that cisplatin exposure led to a downregulation of 28 microRNAs (e.g., miR-519a-3p, miR-181a-5p, miR-374a-5p, miR-98-5p, miR-29c-3p, miR-22-3p, miR-34c-3p, miR-206, miR-429, miR-339-3p, miR-203a, miR-25-3p, miR-155-5p, and miR-148a-3p) by −5.18 to −19.27-fold, and upregulation of 15 microRNAs (e.g., miR-382-3p, miR-485-5p, miR-574-5p, miR92b-3p, miR-297, miR-185-5p, miR-885-3p, miR-194-5p, and miR-630) by 3.95-to 7.46-fold in SCC-11 cells compared with SCC-11M cells upon cisplatin exposure. [36][37][38][39] We further showed that cisplatin exposure altered microRNA expression in SCC-11 cells, resulting in downregulation of 7 microRNAs (e.g., miR-519-a-3p, miR-181a-5p, miR-374a-5p, miR-29c-3p, miR-98-5p, miR-22-3p, and miR-34c-3p, from −1.72 to −3.77-fold), and upregulation of 7 microRNAs (miR-382-3p, miR-485-5p, miR-574-5p, miR-297, miR-194-5p, miR-885-3p, and miR-630, from 2.08-to 4.98-fold), as shown in references 36-39.…”
Section: P-δnp63α-dependent Epi-micrornas Modulate the Expression Of mentioning
confidence: 99%
See 1 more Smart Citation
“…34 By global analysis of microRNA expression, we previously showed that cisplatin exposure led to a downregulation of 28 microRNAs (e.g., miR-519a-3p, miR-181a-5p, miR-374a-5p, miR-98-5p, miR-29c-3p, miR-22-3p, miR-34c-3p, miR-206, miR-429, miR-339-3p, miR-203a, miR-25-3p, miR-155-5p, and miR-148a-3p) by −5.18 to −19.27-fold, and upregulation of 15 microRNAs (e.g., miR-382-3p, miR-485-5p, miR-574-5p, miR92b-3p, miR-297, miR-185-5p, miR-885-3p, miR-194-5p, and miR-630) by 3.95-to 7.46-fold in SCC-11 cells compared with SCC-11M cells upon cisplatin exposure. [36][37][38][39] We further showed that cisplatin exposure altered microRNA expression in SCC-11 cells, resulting in downregulation of 7 microRNAs (e.g., miR-519-a-3p, miR-181a-5p, miR-374a-5p, miR-29c-3p, miR-98-5p, miR-22-3p, and miR-34c-3p, from −1.72 to −3.77-fold), and upregulation of 7 microRNAs (miR-382-3p, miR-485-5p, miR-574-5p, miR-297, miR-194-5p, miR-885-3p, and miR-630, from 2.08-to 4.98-fold), as shown in references 36-39.…”
Section: P-δnp63α-dependent Epi-micrornas Modulate the Expression Of mentioning
confidence: 99%
“…[35][36][37][38][39] Using knock-in technology, we generated SCC-11 cells, which have been shown to produce wild-type ΔNp63α, and SCC-11M cells that exclusively express ΔNp63α-S385G mutant protein, with an altered ability to be phosphorylated by ATM kinase. 34 By global analysis of microRNA expression, we previously showed that cisplatin exposure led to a downregulation of 28 microRNAs (e.g., miR-519a-3p, miR-181a-5p, miR-374a-5p, miR-98-5p, miR-29c-3p, miR-22-3p, miR-34c-3p, miR-206, miR-429, miR-339-3p, miR-203a, miR-25-3p, miR-155-5p, and miR-148a-3p) by −5.18 to −19.27-fold, and upregulation of 15 microRNAs (e.g., miR-382-3p, miR-485-5p, miR-574-5p, miR92b-3p, miR-297, miR-185-5p, miR-885-3p, miR-194-5p, and miR-630) by 3.95-to 7.46-fold in SCC-11 cells compared with SCC-11M cells upon cisplatin exposure.…”
Section: P-δnp63α-dependent Epi-micrornas Modulate the Expression Of mentioning
confidence: 99%
“…[30][31][32] Cisplatin treatment activates autophagy in multiple cancer cells and decreases the level of several miRNAs at the same time, which target multiple key regulators in autophagy, such as miR-199a-5p against ATG7 in HCC, 33 miR-181a and miR-374a against ATG5, miR-630 against ATG12 and miR-519a against beclin-1, ATG10 and ATG16 in squamous cell carcinoma (SCC) cells. 34 The miRNA-mediated genes and pathways involved in autophagy are illustrated in Figure 1. feedback loop between p53 and miR-502.…”
Section: Mirnas Mediated Autophagy In Genotoxic Stress and Hypoxiamentioning
confidence: 99%
“…Cisplatin has been shown to induce autophagy in cancer cells 33,34 and activate p53 family members, 42,43 which, in turn, function as transcriptional regulators to affect downstream gene expression, including miRNAs. [44][45][46] In SCC cells, cisplatin exposure phosphorylates ΔNp63α, which directly regulates the transcription of many miRNAs.…”
Section: Mirna: the Third Dimension Of P53-mediated Autophagymentioning
confidence: 99%
See 1 more Smart Citation